Digital Fabrication and Theater: Developing Social Skills in Young Adults With Autism Spectrum Disorder - Sandoval Poveda, Alicia; Hernández Montoya, Diana (Frontiers in Psychology, 2021)
An action research project was carried out, using theater workshops and basic digital fabrication technology workshops to improve social skills – such as the expression of emotions, communication, self-control, and teamwork – in a group of ten young individuals with autism spectrum disorder (ASD). This article focuses on the digital fabrication workshops, where participants worked on the fundamentals of electronics and programming, as well as 3D design and printing, to make props that were later used on stage in the theatrical performances in which they participated. These workshops were systematized through observation guides. According to the results, it was evident that the participants not only enjoyed and gained technological knowledge, but that their social skill development needs were addressed. Professionals from the Special Education Faculty and the Fab Lab Kä Träre, both from Universidad Estatal a Distancia in Costa Rica, were in charge of the study.